Development of Football Bowling Game for Football Learning Approaches (Department of Physical Education, Sport, Health and Recreation, 2019)
This research is motivated by the lack of adequate football and goal fields, so there is a need for modification in learning so that the learning process can be carried out more effectively. Modifications in learning include making the game a football learning approach that is adapted to conditions on the field. The purpose of this study is to develop a bowling football game model that can be used as an alternative approach to football learning. This research was conducted using research and development using the ADDIE model, namely analysis, design, development, implementation, evaluation. The sampling technique used saturated sampling to determine the sample of this study is using eighteen fifth grade students of MI Fastabiqul Khoirot Jambu for field tests. Before being tested on students, this game model has been validated by physical education learning experts and football game experts. The research data collection instrument used was a questionnaire. The data analysis technique of this research is qualitative and quantitative descriptive percentages. The results of field test data analysis, obtained an average of 82%. Based on the criteria that have been obtained from the field test results, the product development of this bowling football game meets the criteria can be used. So it can be concluded that this bowling football game can be used and applied as an alternative approach to football learning in fifth grade students of MI Fastabiqul Khoirot Jambu.